Power flow control capability of the power transistor-assisted Sen transformer and the unified power flow controller: a close comparison - Gasim Mohamed, Salah Eldeen (IET generation, transmission & distribution, 2020)
Currently, transmission grids are subject to experience more operation and control difficulties. The use of power flow controllers (PFCs) can ease such difficulties. However, most competent PFCs need to be used. Cost-wise, the power transistor assisted Sen transformer (TAST) is attractive as compared to the unified PFC (UPFC). However, while the UPFC has three control parameters, the TAST has only two. The UPFC can regulate the voltage of its shunt bus while the TAST cannot. The main objective of this study is to investigate the extent to which the TAST and UPFC are comparable when used for power flow control. Power flow control is performed in this study for congestion management using a TAST/UPFC in a modified IEEE-118 bus system. A TAST/UPFC is optimally located using sensitivity analysis. For the sake of validation, results are obtained using both load flow analysis and voltage vector analysis. With only two control parameters, the performance of the TAST is found very closely comparable to that of the UPFC. Accordingly, the TAST can competently replace the UPFC for application of power flow control, at a far lower cost. Nonetheless, appropriate limited angle TAST is a suitable substitute for the TAST at a further lower cost.